Researching with integrity : the ethics of academic enquiry - Macfarlane, Bruce (Routledge, 2009)
"Researching with Integrity breaks new ground by analyzing research ethics from the perspective of individual character rather than rule based codes of practice. It challenges over-dependence on principles derived from bioethics to produce a book with relevance to a wide range of academic disciplines. Reflecting on real stories from university academics to illustrate fine-grained research dilemmas, it identifies a series of moral virtues for the modern researcher and attendant vices to be avoided. The virtues of courage, respectfulness, resoluteness, sincerity, humility, and reflexivity are closely related to ethical practice throughout different phases of research in framing questions, negotiating access, generating data and ideas, creating results, disseminating those results, and reflecting on what has been achieved. The book offers a theoretically grounded yet strongly practical approach to understanding the complexities of research ethics. As such it will be an essential resource for both serious scholars of research ethics and postgraduate students."--BOOK JACKET.